Analysis of The Influence of Government Revenue and Expenditure on Economic Growth in Indonesia - Sri Fanny Utari; Abdiyanto; Kiky Hardiansyah Siregar (Yayasan Multidimensi Kreatif, 2024)
This study aims to Analyze Income and Expenditure on Economic Growth in Indonesia. Where there are bound variables, namely GDP (Gross Domestic Product) and there are two independent variables, namely Government Revenue and Expenditure. This study uses secondary data by searching for data through the Central Statistics Agency (BPS) Website and the Indo Data Website. The data analysis model in this study uses multiple linear regression. The results of the study show that the Inclusion Variable of Government Revenue and Expenditure has a significant effect on GDP (Gross Domestic Product).GDP (Gross Domestic Product)